Psychometric assessment of the Italian version of the melanoma module (SCNS-M12-Ita) of the Supportive Care Needs Survey (SCNS-SF34). Issue 2 (April 2020) - Miniotti, Marco; Zeneli, Anita; Bassino, Stefania; Pavan, Sara; Ribero, Simone; Leombruni, Paolo
Introduction: This study examines the validity and the reliability of the translated-into-Italian version of the SCNS-SF34 melanoma module (SCNS-M12-Ita) for a sample of patients with melanoma ( n = 268). Methods: Content validity was analyzed by examining the redundancy of items. Floor/ceiling effects were investigated via frequency tables. Factor structure was studied through principal component analysis. Internal consistency was evaluated with Cronbach α. Test–retest reliability was analyzed using intraclass correlation coefficients (ICCs). Convergent–discriminant validity was studied by calculating Pearson correlations. Construct validity was investigated by comparing subgroups of patients through multivariate analysis of variance. Results: Content validity of the SCNS-M12-Ita was satisfactory. The floor effect ranged from 24.3% to 82.5%. The 2-factor solution explained 61.4% of the total variance. Internal consistency was excellent for component 1 (α = 0.92) and questionable (α = 0.58) for component 2. Test–retest reliability was excellent for component 1 (ICC = 0.92) and poor for component 2 (ICC = 0.58). Except for component 2, item-total correlations were greater than 0.60. Construct validity was confirmed, as the expected correlations ( r < 0.40) were observed and 60% of the postulated hypotheses about between-group differences were confirmed. Conclusions: The study demonstrated that the SCNS-M12-Ita is a valid and reliable instrument for assessing the supportive care needs of patients with melanoma.